The physical fitness of Iloilo public school girls ages 11-15 - Corral, Cecilia P. 1937- (s.n.], 1973)
The physical fitness status of Iloilo Public School girls aged 11-15 was compared with the Philippine fitness norms. Areas of physical fitness deficiences of this particular age groups were determined.